The Efficacy and Safety of Topical Gel Formulation of n-Hexane Fraction of Curcuma longa in Wound Healing of Hyperglycemic Mice - Wientarsih, Ietje; Winarsih, Wiwin; Sutardi, Lina Noviyanti (Jurnal Veteriner; Vol 14 No 1 (2013), 2013)
Curcuma longa (turmeric) is one of the tropical plant belong to Zingiberaceae family. It has beneficialeffects in healing of variety diseases. The aim of this study was to evaluate the efficacy and safety of  atopical gel formulation of n-hexane fraction of Curcuma longa in the wound healing of hyperglycemic mice.A total of 30 hyperglycemic mice were divided into three groups. They were given topical application, NC asa negative control (gel base), PC as a positive control (Neomycine sulfate 5%), treated groups (HF = n-hexane gel). Histopathological examination of the skin was performed to evaluate the wound healing.  Theresult showed that, there were no changes on tha appearance of the gel preparation, physically.  Evethoughupon the pH determination of the gel at six month of storage at 40ºC there were significant difference.  Theeffect of n-hexane gel, in terms of decreasing the surface area of wound and histopathological characteristicswere significantly (p <0.05) different between the PC group and HF group.  Skin irritant test showedneither rashes, swelling, inflammation, redness, irritation, itching nor any other toxicity  symptoms followingapplication of the gel. Significant effect of n hexane fraction of C. longa gel on wounds without any adversedermal toxic effects sounds very promising and it may be employed in the management of diabetic wound.
Keywords: turmeric, n-hexane, wound, hyperglycemic